THE INVESTIGATION OF THE STRUCTURE OF THE SIGNAL OF GEOPHYSICAL AND ASTROPHYSICAL ORIGIN IN THE ELECTROMAGNETIC FIELD OF THE ATMOSPHERE BOUNDARY SURFACE LAYER - Grunskaya, L.; Isakevich, V.; Yefimov, V.; Zakirov, A.; Rubay, D.; Leshchev, I. (Одеські астрономічні публікації, 2012)
There has been developed a program - analytical system for investigation the structure of the signal in the spectral and time ranges caused by geophysical processes. The main purpose of developing such system is - to investigate the structure of the signal in the spectral and time ranges, caused by geophysical and astrophysical magnetic field of the atmosphere boundary surface layer and to find under - noise periodical processes of geophysical nature. The analysis of the exposing efficiency in the time ranges of the components corresponding to the periods of the moon gravitational tides showed high efficiency of the eigen vectors, chosen according to the criterion MKK which provides very slight probably of the false alarm of omitting displayed signs at the level 10-4.